2017
DOI: 10.30738/.v5i2.1085
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Pembelajaran Matematika Realistik Terhadap Kemampuan Pemahaman Matematis dan Keyakinan Diri Siswa SMP

Abstract: Rendahnya kemampuan pemahaman matematis dan keyakinan diri siswa menyebabkan siswa kesulitan dalam memahami materi dan menyelesaikan permasalahan, sehingga siswa merasa takut akan pelajaran matematika yang diyakini terasa sulit. Penelitian ini bertujuan untuk mengetahui pengaruh pembelajaran matematika realistik terhadap kemampuan pemahaman matematis dan keyakinan diri siswa. Metode penelitian yang dilakukan adalah quasi eksperimen dengan populasi seluruh siswa kelas VII SMP Negeri 14 Kota Cirebon. Teknik peng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 2 publications
1
4
0
1
Order By: Relevance
“…The results of the data analysis show that the RME approach provides equal opportunities for students to solve contextual problems for both students who have high self-efficacy and students who have low self-efficacy. This is in line with the opinion of Zulkardi (Nursiddik, Noto, & Hartono, 2017) which states that the RME approach is a teaching approach that starts from real things for students, emphasizes the skills of the process of doing mathematics, discussing and collaborating, arguing with classmates so that they can find own strategies or ways of solving problems and in the end using mathematics to solve problems, either individually or in groups. high self-efficacy always want to show their ability to solve problems and when given difficult questions that have never been encountered before, they are instead used as challenges and are motivated to find solutions as a challenge.…”
Section: Resultssupporting
confidence: 82%
“…The results of the data analysis show that the RME approach provides equal opportunities for students to solve contextual problems for both students who have high self-efficacy and students who have low self-efficacy. This is in line with the opinion of Zulkardi (Nursiddik, Noto, & Hartono, 2017) which states that the RME approach is a teaching approach that starts from real things for students, emphasizes the skills of the process of doing mathematics, discussing and collaborating, arguing with classmates so that they can find own strategies or ways of solving problems and in the end using mathematics to solve problems, either individually or in groups. high self-efficacy always want to show their ability to solve problems and when given difficult questions that have never been encountered before, they are instead used as challenges and are motivated to find solutions as a challenge.…”
Section: Resultssupporting
confidence: 82%
“…From the analysis of data with the help of CMA software, the Rosenthal safe N value is 33411. According to the formula N / (5k + 10) (Nursiddik et al, 2017) that is 33411 / (5 * 95 + 10), the calculation results are 68,889. According to this calculation, it can be identified that the studies included in this analysis are resistant to publication bias.…”
Section: Reliability Testmentioning
confidence: 99%
“…Various studies have found the application of RME in Indonesia affects the mathematical abilities of students (Hasratuddin, 2010;Putri, 2011;Artawa, Wyn, & Suwatra, 2012;Palinussa, 2013;Rohmah, Caswita, & Widyastuti, 2014;Rohman & Sugiman, 2015;Yunisha, Prahmana, & Sukmawati, 2016;Nursiddik, Noto, & Hartono, 2017;Dwi Yanti, Wahyu Widada, & Zamzaili, 2018;Husniyah, Sulistiani, & Mustafida, 2019). However, to date in the literature, no comprehensive evaluation has been carried out on the effect of RME on students' mathematical abilities.…”
Section: A Introductionmentioning
confidence: 99%
“…Several previous studies that have conducted research with the same title have obtained different results, such as one of the leading researchers. According to Nursiddik, Noto and Hartono (2017), in the results of this study there is an effect of using realistic mathematics learning on students' mathematical understanding abilities in 7 th grade of Junior High School 14 Cirebon. This can be seen in the results of students' mathematical understanding abilities who use realistic mathematics learning which is higher than the mathematical comprehension abilities of students who use conventional learning.…”
Section: Description Of the Difference In The Ability Of Mathematical Connection And Self Efficacy Between Students Given A Realistic Matmentioning
confidence: 68%